Philippine house consolidation estimating changes in housing quality - Jimenez, Emmanuel Y. (1981)
The National Housing Authority has been instrumental in effecting physical improvements in the residences of Tondo, Metro Manila's most congested squatter community. The impressive pictorial records and tables indicative of the changes in housing quality in this slum district are analyzed in terms of statistical measures of up- grading dwelling units. The use of the hedonic pricing technique to obtain a price- consistent measure of change in housing quality is also described. The method anchors on the assumption that a house is a bundle of size, quality and location characteristics, and that the rent or value of a housing unit stems from the quality and type of characteristics it contain
Keywords: Public housing aspects; Squatters -- Social conditions; National Housing Authority (NHA); Housing rehabilitation